Anti-atherosclerotic Effects of Eurycoma Longifolia (Tongkat Ali) in Rats Fed on High-fat Diet - Al-Joufi, F; Saxena, AK; Al-Ani, IM; Talib, NA; Mokhtar, RH; Ku-Zaifah, N (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/ Scopus